2006
DOI: 10.1086/506454
|View full text |Cite
|
Sign up to set email alerts
|

β‐Defensin Gene Expression during the Course of Experimental Tuberculosis Infection

Abstract: The kinetics of gene expression and the cellular source of murine beta -defensin-3 (mBD3) and murine beta -defensin-4 (mBD4) were determined in mouse models of progressive pulmonary tuberculosis and latent infection induced by high or low infecting doses, respectively. During progressive disease, there was an initial rapid expression of both defensins by respiratory epithelial cells that correlated with temporary control of bacillary proliferation, but expression decreased during the later progressive phase of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
90
1
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 82 publications
(98 citation statements)
references
References 15 publications
6
90
1
1
Order By: Relevance
“…We also studied the expression of mBD-4 as a significant factor of innate immunity. In this animal model, when infected with M. tuberculosis, H37Rv mBD-4 seems to have a significant role in the control of bacillary growth [20]. Interestingly, infection with either 04-303 or 04-302 induced very low mBD-4 expression, whereas the control strain AN5 induced progressively increasing expression of this anti-microbial peptide, peaking at day 120 (Fig.…”
Section: Differences In Immune Responses Evoked By Different M Bovismentioning
confidence: 81%
See 3 more Smart Citations
“…We also studied the expression of mBD-4 as a significant factor of innate immunity. In this animal model, when infected with M. tuberculosis, H37Rv mBD-4 seems to have a significant role in the control of bacillary growth [20]. Interestingly, infection with either 04-303 or 04-302 induced very low mBD-4 expression, whereas the control strain AN5 induced progressively increasing expression of this anti-microbial peptide, peaking at day 120 (Fig.…”
Section: Differences In Immune Responses Evoked By Different M Bovismentioning
confidence: 81%
“…In this animal model, we have shown that after infection with strain M. tuberculosis H37Rv there is rapid and high expression of mBD-4 during the early phase, while there is efficient control of bacillary replication. Then, during the progressive phase, there is a pronounced decrease in expression of mBD-4, while proliferation of the bacilli increases [20]. Thus, the low expression of mBD-4 in mice infected with highly virulent M. bovis strains could contribute to a high rate of bacillary replication and extensive tissue damage.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…CRAMP expression was high in the progressive phase of the disease and the protein was observed in different structures of the mycobacteria. The authors of these studies conclude that both defensins and cathelicidin participate in mycobacterial containment, not only by the direct activity against the bacteria, but by their recognized chemotactic activity (Rivas-Santiago et al, 2006;Castañeda-Delgado et al, 2010). Another antimicrobial peptide involved in the defense against M. tuberculosis is hepcidin.…”
Section: Innate Immune Response Of Non-phagocytic Infected By M Tubementioning
confidence: 99%